(Don’t) Use Your Hands: The South Levantine Late Chalcolithic (ca. 4500–3900 cal BC) Spoons and Their Significance - Danny Rosenberg; Shira Gur-Arieh; Motti Pearl; Hadar Ahituv (Humans, 2024)
The Late Chalcolithic period in the southern Levant saw notable changes in almost every aspect of daily life. Some of the most significant shifts during this time seem to have been anchored in the subsistence economy and involved food and its cooking, processing, storage, serving, and handling with vessels and tools. The paper offers a comprehensive overview and analysis of one utensil that is likely to have been caught up in these developments—the Late Chalcolithic spoon. While spoons first appeared in the region during the Pottery Neolithic period, the Chalcolithic period witnessed a rise in their frequency and distribution. Nonetheless, they were few in number. While their functions remain unclear, we have presupposed their association with food and kitchenware and have explored them in this vein. This paper delves into their morphological characteristics and distribution and ponders their significance in light of other changes that occurred during the Late Chalcolithic period in the southern Levant.